Pengaruh Budaya Organisasi, Extrinsic Reward dan Loyalitas Kerja terhadap Kinerja Karyawan PT. Suzuki Indomobil Sales - Jessica Angelia; Ika Suhartanti Darmo (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Human resources play a very dominant role in the progress of automotive business companies amid increasingly fierce competition. The performance of employees in organizations leads to the ability of employees to carry out the overall tasks that are the responsibility. This study aims to determine whether there is an influence between Organizational Culture, Extrinsic Reward and Work Loyalty on Employee Performance at PT. Suzuki Indomobil Sales. This study uses a quantitative approach through the distribution of questionnaires to 100 employees of PT. Suzuki Indomobil Sales. Hypothesis test results (t test) indicate that organizational culture variables do not affect employee performance variables. Extrinsic rewards variable has a significant effect on employee performance. Likewise, work loyalty has a significant effect on employee performance variables. Simultaneously the variables of organizational culture, extrinsic reward and work loyalty have significant and significant effects on employee performance. Researchers suggest that PT. Suzuki Indomobil Sales pays more attention to these three factors because they are proven to affect employee performance, especially for organizational culture variables.